A COMPARISON OF THE EDUCATIONAL THOUGHTS OF R.A KARTINI AND MALALA YOUSAFZAI - Imam Ghozali; Syarif Hidayatullah; Thriska Afifandasari (Universitas Labuhanbatu, 2023)
R.A Kartini and Malala Yousafzai are women who are very vocal in fighting for women's rights, including in terms of education. But what's more interesting, they live in very different times and environmental backgrounds but have their own passion and thoughts about education. The purpose of this research is to compare the thoughts of the two figures. This type of research is library research. While the method of analysis is content analysis, reduction and interpretation. This research shows the similarity of Kartini's thoughts with Malala, namely one of them is pro towards educational equality while what distinguishes them is their basis and approach in formulating the concept of the urgency of education for women. R.A Kartini and Malala are two smart and brave girls who have high empathy and social sensitivity. This character is their foundation in fighting for women's education.Keywords: Comparison, Education, Malala Yousafzai, R.A. KartiniAbstrakR.A Kartini dan Malala Yousafzai merupakan perempuan yang sangat vocal dalam memperjuangkan hak-hak perempuan termasuk dalam hal pendidikan. Namun yang lebih menarik, mereka hidup di zaman dan latar belakang lingkungan yang jauh berbeda namun memiliki semangat serta pemikiran masing-masing tentang pendidikan. Tujuan dari penelitian ini untuk mengetahui perbandingan pemikiran kedua tokoh tesebut. Jenis penelitan ini adalah libtary research. Sedangkan metode analisisnya adalah content analisys, reduksi dan interpretasi. Penelitian ini menunjukkan kemiripan pemikiran Kartini dengan Malala yakni salah satunya pro terhadap kestaraan pendidikan sedangkam yang membedakannya dasar dan pendekatan mereka dalam merumuskan konsep urgensi pendidikan untuk perempuan. R.A Kartini dan Malala adalah dua gadis cerdas dan pemberani yang memiliki empati serta kepekaan sosial yang tinggi. Karakter tersebut yag menjadi landasan mereka dalam memperjuangkan pendidikan perempuan.Kata Kunci : Perbandingan, Pendidikan, Malala Yousafzai, R.A. Kartini